Single-Photon Emission Computed Tomographic Imaging of the Early Time Course of Therapy-Induced Cell Death Using Technetium 99m Tricarbonyl His-Annexin A5 in a Colorectal Cancer Xenograft Model - Christel Vangestel; Christophe Van de Wiele; Gilles Mees; Koen Mertens; Steven Staelens; Chris Reutelingsperger; Patrick Pauwels; Nancy Van Damme; Marc Peeters (Molecular Imaging)
As apoptosis occurs over an interval of time after administration of apoptosis-inducing therapy in tumors, the changes in technetium 99m ( 99m Tc)-tricarbonyl (CO) 3 His-annexin A5 (His-ann A5) accumulation over time were examined. Colo205-bearing mice were divided into six treatment groups: (1) control, (2) 5-fluorouracil (5-FU; 250 mg/kg), (3) irinotecan (100 mg/kg), (4) oxaliplatin (30 mg/kg), (5) bevacizumab (5 mg/kg), and (6) panitumumab (6 mg/kg). 99m Tc-(CO) 3 His-ann A5 was injected 4, 8, 12, 24, and 48 hours posttreatment, and micro–single-photon emission computed tomography was performed. Immunostaining of caspase-3 (apoptosis), survivin (antiapoptosis), and LC3-II (autophagy marker) was also performed. Different dynamics of 99m Tc-(CO) 3 His-ann A5 uptake were observed in this colorectal cancer xenograft model, in response to a single dose of three different chemotherapeutics (5-FU, irinotecan, and oxaliplatin). Bevacizumab-treated mice showed no increased uptake of the radiotracer, and a peak of 99m Tc-(CO) 3 His-ann A5 uptake in panitumumab-treated mice was observed 24 hours posttreatment, as confirmed by caspase-3 immunostaining. For irinotecan-, oxaliplatin-, and bevacizumab-treated tumors, a significant correlation was established between the radiotracer uptake and caspase-3 immunostaining ( r = .8, p < .05; r = .9, p < .001; r = .9, p < .001, respectively). For 5-FU- and panitumumabtreated mice, the correlation coefficients were r = .7 ( p = .18) and r = .7 ( p = .19), respectively. Optimal timing of annexin A5 imaging after the start of different treatments in the Colo205 model was determined.